Highly Efficient 2D/3D Mixed-Dimensional Cs2PbI2Cl2/CsPbI2.5Br0.5 Perovskite Solar Cells Prepared by Methanol/Isopropanol Treatment - Bicui Li; Shujie Yang; Huifang Han; Huijing Liu; Hang Zhao; Zhenzhen Li; Jia Xu; Jianxi Yao (Nanomaterials, 2023)
All-inorganic perovskite solar cells are attractive photovoltaic devices because of their excellent optoelectronic performance and thermal stability. Unfortunately, the currently used efficient inorganic perovskite materials can spontaneously transform into undesirable phases without light-absorption properties. Studies have been carried out to stabilize all-inorganic perovskite by mixing low-dimensional perovskite. Compared with organic two-dimensional (2D) perovskite, inorganic 2D Cs2PbI2Cl2 shows superior thermal stability. Our group has successfully fabricated 2D/3D mixed-dimensional Cs2PbI2Cl2/CsPbI2.5Br0.5 films with increasing phase stability. The high boiling point of dimethyl sulfoxide (DMSO) makes it a preferred solvent in the preparation of Cs2PbI2Cl2/CsPbI2.5Br0.5 inorganic perovskite. When the perovskite films are prepared by the one-step solution method, it is difficult to evaporate the residual solvent molecules from the prefabricated films, resulting in films with rough surface morphology and high defect density. This study used the rapid precipitation method to control the formation of perovskite by treating it with methanol/isopropanol (MT/IPA) mixed solvent to produce densely packed, smooth, and high-crystallized perovskite films. The bulk defects and the carrier transport barrier of the interface were effectively reduced, which decreased the recombination of the carriers in the device. As a result, this effectively improved photoelectric performance. Through treatment with MT/IPA, the photoelectric conversion efficiency (PCE) of solar cells prepared in the N2 atmosphere increased from 13.44% to 14.10%, and the PCE of the device prepared in the air increased from 3.52% to 8.91%.